Liuwei Dihuang formula ameliorates chronic stress-induced emotional and cognitive impairments in mice by elevating hippocampal O-GlcNAc modification - Huang, Yan; Wang, Jianhui; Liu, Feng; Wang, Chenran; Xiao, Zhiyong; Zhou, Wenxia (Frontiers in Neuroscience, 2023)
A substantial body of evidence has indicated that intracerebral O-linked N-acetyl-β-D-glucosamine (O-GlcNAc), a generalized post-translational modification, was emerging as an effective regulator of stress-induced emotional and cognitive impairments. Our previous studies showed that the Liuwei Dihuang formula (LW) significantly improved the emotional and cognitive dysfunctions in various types of stress mouse models. In the current study, we sought to determine the effects of LW on intracerebral O-GlcNAc levels in chronic unpredictable mild stress (CUMS) mice. The dynamic behavioral tests showed that anxiety- and depression-like behaviors and object recognition memory of CUMS mice were improved in a dose-dependent manner after LW treatment. Moreover, linear discriminate analysis (LEfSe) of genera abundance revealed a significant difference in microbiome among the study groups. LW showed a great impact on the relative abundance of these gut microbiota in CUMS mice and reinstated them to control mouse levels. We found that LW potentially altered the Uridine diphosphate-N-acetylglucosamine (UDP-GlcNAc) biosynthesis process, and the abundance of O-GlcNAcase (OGA) and O-GlcNAc transferase (OGT) in CUMS mice, which was inferred using PICRUSt analysis. We further verified advantageous changes in hippocampal O-GlcNAc modification of CUMS mice following LW administration, as well as changes in the levels of OGA and OGT. In summary, LW intervention increased the levels of hippocampal O-GlcNAc modification and ameliorated the emotional and cognitive impairments induced by chronic stress in CUMS mice. LW therefore could be considered a potential prophylactic and therapeutic agent for chronic stress.